Paratanytarsus Thienemann & Bause from China (Diptera: Chironomidae: Tanytarsini) - Wang, Xinhua; Guo, Yuhong (Zootaxa, 2005)
This article reviews the Tanytarsini genus Paratanytarsus from China. Paratanytarsus paralauterborni is described as new to science. The male of an unnamed species (sp. A) also is described. Two newly recorded species from China — P. inopterus (Walker) and P. tenuis (Meigen) — and P. dissimilis (Johansen) are redescribed and figured as males. The female of P. grimmii (Schneider) is reexamined and illustrated. A key to the males of the Chinese Paratanytarsus is given.